Evaluating the Effect of Novel Ways of Teaching Symptoms and Treatment of Acute Stroke on Thrombolytic Therapy - Rafie, Shahram; Kashipazha, Davood; Sabahi, Navid (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Background and Objective: Given that a small percentage of people with ischemic stroke are treated with recombinant tissue plasminogen activator (rtPA) in Iran, it is necessary to use appropriate educational methods that, in addition to raising the awareness of patients about stroke, lead them to refer health centres early. The purpose of this study was to evaluate the effect of new methods of training warning signs of acute stroke on thrombolytic therapy. Method: This was a community-based empirical intervention study in Ahvaz, Iran, in 2018. Initially, educational content was provided, including warning signs of a stroke, its risk factors, and the need for prompt referral to a well-equipped treatment centre for thrombolytic therapy. This content was used to prepare brochures, pamphlets, posters, and training sessions for health care personnel. Before starting, immediately, and three months after the training course, a questionnaire was used to assess staff knowledge of stroke symptoms and the need for rapid patient referral for FAST-based thrombolytic therapy. Also, the timely referral of patients with suspected stroke to hospital, as well as their thrombolytic therapy during the six months after the intervention and the similar six months in the previous year were compared. Results: The level of knowledge was significantly increased at the end of training (P<0.0001). Although this average was reduced three months after completion of training, the difference was not significant (P = 0.42). Based on the results, the number of stroke patients referred to hospital in golden time (less than 4.5 hours) from the beginning of training to 6 months after the end of the course (n = 54) was increased compared to the same period last year (n=38). The number of thrombolytic patients from the beginning of the training course to 6 months after the course (n=38) increased compared to the same period of the previous year (n=21). Conclusion: Based on the results, the implementation of educational programs was reported to be effective in raising public awareness of stroke symptoms and the need for prompt hospital referral for appropriate and timely treatment.